2017
DOI: 10.1158/0008-5472.can-16-2263
|View full text |Cite
|
Sign up to set email alerts
|

The Alkylating Chemotherapeutic Temozolomide Induces Metabolic Stress in IDH1-Mutant Cancers and Potentiates NAD+ Depletion–Mediated Cytotoxicity

Abstract: IDH1 -mutant gliomas are dependent upon the canonical coenzyme nicotinamide adenine dinucleotide (NAD+) for survival. It is known that Poly(ADP-ribose) polymerase (PARP) activation consumes NAD+ during base excision repair (BER) of chemotherapy-induced DNA damage. We therefore hypothesized that a strategy combining NAD+ biosynthesis inhibitors with the alkylating chemotherapeutic agent temozolomide (TMZ) could potentiate NAD+ depletion-mediated cytotoxicity in mutant IDH1 cancer cells. To investigate the impac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 37 publications
(43 reference statements)
5
59
1
Order By: Relevance
“…We did not identify a similar association in a panel of human chondrosarcoma cell lines. Likewise, the synthetic lethal interaction between temozolomide and IDH mutations described in gliomas was not observed in our study [35,36]. Our research group published that the reported synthetic lethal interaction between IDH mutations and Bcl-2, NAMPT, and glutaminase inhibition was absent in chondrosarcoma [11,[37][38][39].…”
Section: Discussioncontrasting
confidence: 49%
“…We did not identify a similar association in a panel of human chondrosarcoma cell lines. Likewise, the synthetic lethal interaction between temozolomide and IDH mutations described in gliomas was not observed in our study [35,36]. Our research group published that the reported synthetic lethal interaction between IDH mutations and Bcl-2, NAMPT, and glutaminase inhibition was absent in chondrosarcoma [11,[37][38][39].…”
Section: Discussioncontrasting
confidence: 49%
“…In addition to developing rational combination regimens using NAMPT inhibitors, careful patient selection represents an additional opportunity to maximize the efficacy of these agents. For example, IDH mutant cancers have been shown to have exquisite sensitivity to NAMPT inhibitors (63)(64)(65), as have tumors deficient in NAPRT (9,(145)(146)(147)(148)(149)(150)(151). Patient selection may also be guided by recognition of specific vulnerabilities in the non-metabolic pathways supported by NAMPT, such as HR-deficiency or EMT targeting for metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Given these insights, a number of studies have sought to determine the efficacy of NAMPT inhibitors when combined with DNA damaging agents. Enhanced antitumor activity has been reported across multiple malignancies when genetic or pharmacological inhibition of NAMPT has been combined with radiation (101), DNA alkylating agents (63,99,100,102,103), topoisomerase inhibitors (19,46,86), or other classes of chemotherapy known to augment the effects of impaired DNA repair (19,20,43,46,(104)(105)(106). Surprisingly, in some cancers, an improvement in efficacy was restricted to combinations with only certain chemotherapeutic agents, as in preclinical studies in pancreatic cancer models which revealed that gemcitabine, but not 5-fluorouracil (5-FU) or oxaliplatin, enhanced the antiproliferative effect of NAMPT inhibitors (107).…”
Section: Dna Damage Repair Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The first two usually do not induce cytotoxicity, because poly (ADP-ribose) polymerase (PARP) activation allows for base excision repair of damaged DNA. Inhibition of PARP or depletion of NAD + , which is a co-enzyme of PARP, leads to cell death (3,44). A previous study has shown PARP1 expression in DIPG cell lines (45).…”
Section: Future Directionsmentioning
confidence: 99%